Development of an overactive bladder assessment tool (BAT): A potential improvement to the standard bladder diary. Issue 5 (23rd January 2018) - Kelleher, Con; Chapple, Christopher; Johnson, Nathan; Payne, Christopher; Homma, Yukio; Hakimi, Zalmai; Siddiqui, Emad; Evans, Christopher; Egan, Shayna; Kopp, Zoe
Abstract : Aims: To develop a comprehensive patient‐reported bladder assessment tool (BAT) for assessing overactive bladder (OAB) symptoms, bother, impacts, and satisfaction with treatment. Methods: Subjects were consented and eligibility was confirmed by a recruiting physician; subjects were then scheduled for in‐person interviews. For concept elicitation and cognitive interviews, 30 and 20 subjects, respectively, were targeted for recruitment from US sites. All interviews were conducted face‐to‐face, audio‐recorded, transcribed verbatim, anonymized, and analyzed using a qualitative data analysis software program. A draft BAT was created based on the results of the concept elicitation interviews and further revised based on cognitive interviews as well as feedback from an advisory board of clinical and patient‐reported outcome (PRO) experts. Results: Nocturia, daytime frequency, and urgency were reported by all subjects ( n  = 30, 100.0%), and incontinence was reported by most subjects ( n  = 25, 83.3%). The most frequently reported impacts were waking up to urinate ( n  = 30, 100.0%), embarrassment/shame ( n  = 24, 80.0%), stress/anxiety ( n  = 23, 76.7%), and lack of control ( n  = 23, 76.7%). Following analysis, item generation, cognitive interviews, and advisory board feedback, the resulting BAT contains four hypothesized domains (symptom frequency, symptom bother, impacts, and satisfaction with treatment) and 17 items with a 7‐day recall period. Conclusions: The BAT has been developed in multiple stages with input from both OAB patients and clinical experts following the recommended processes included in the FDA PRO Guidance for Industry. Once fully validated, we believe it will offer a superior alternative to use of the bladder diary and other PROs for monitoring OAB patients in clinical trials and clinical practice.